Impacts of Online Payment Systems on Consumers and Merchants - Pratham Naik; Yash Kotak; Jaydev Dhanak; Dhwanit Shah; Rahul Chauhan; Andino Maseleno; R Rizal Isnanto (Siber Journal of Transportation and Logistics, 2024)
This study investigates the effects of digital payment systems on consumer behaviours and merchant operations in Ahmedabad. The research is guided by two objectives: analysing the impact of consumer trust on the adoption of digital payment systems, and evaluating the role of these systems in enhancing merchant efficiency and financial performance. Data was collected from 110 respondents using a structured questionnaire, with statistical analysis conducted using SPSS. The results highlight a significant positive relationship between consumer trust and digital payment adoption. Additionally, the implementation of digital payment systems improves operational efficiency for merchants. The study underscores the importance of trust, reliability, and security in fostering adoption and the growing role of digital payment technologies in transforming business operations. Future research should explore long-term impacts and the role of emerging technologies in digital payments.